Empirical Study of the Implicit Theory of Mind of Persons Addicted to Psychoactive Substances - Krupelnytska, Liudmyla; Telcharov, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article is dedicated to empirical investigation of Theory of Mind of persons dependent on psychoactive substances. Searching new approaches to medical treatment, psychological and social rehabilitation retains an actual subject of scientific interest. Inclusion of the Theory of Mind to rehabilitation and corrective programs can be a perspective direction. The purpose of this article is to analyze the Theory of Mind peculiarities in persons who are addicted to psychoactive substances, as well as to determine the interconnection between the Theory of Mind, alexithymia, and personality dispositions. The following methods have been used: Theory of Mind assessment scale (Th.o.m.a.s), Toronto Alexithymia Scale (TAS-26), Big Five Personality Test (5PFQ). Statistical tools: descriptive statistics and non-parametric (Spearman’s correlation coefficient, Mann-Whitney U test). Study sample – 32 persons, who are addicted to psychoactive substances (median 41 y.o., SD 11,83). As a result of this empirical study, we have found several peculiarities of the Theory of Mind in persons dependent on psychoactive substances. We have compared this result to previous findings obtained by authors of the Th.o.m.a.s test. There were determined the number of connections between the Theory of Mind and other psychological features. Theory of Mind in persons dependent on psychoactive substances is characterized by a reduced understanding of their own emotions and feelings. This appears as poor differentiation of emotional experiences and physiological manifestations of the body. Another peculiarity of Theory of Mind dependent on psychoactive substances is a poor allocative perspective. It means that dependent on psychoactive substances cannot or do not want to «walk in someone else’s shoes», this is why they project their own beliefs.
Keywords: alexithymia; Theory of Mind; dependent on psychoactive substances; empirical research; personality traits